Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

What Should Ministries of Education Prioritise When Crafting Their Edtech Strategies? - Thinley, Sangay (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at priorities for governments and ministries of education when crafting EdTech Strategies. Interest in developing EdTech strategies related to operational targets and outcomes has increased over the past few years, especially in response to the learning disruptions caused by the Covid-19 pandemic. Evidence suggests that countries with established EdTech strategies were better equipped to respond to the pandemic and its effects due to their advanced preparation and readiness for large-scale remote learning. We examine the key principles for EdTech strategies, including the importance of focusing on learning outcomes, inclusivity, teacher training, costs, and contextual needs, among other factors. We draw on EdTech Hub's work in supporting several governments in designing and implementing EdTech strategies, as well as broader evidence from the field, to offer practical insights. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt, such as prioritising consultative processes of strategy development while focusing on multi-modal, problem-driven EdTech solutions and interventions guided by a unifying educational goal. We highlight areas that require further research, in particular questions related to cost-effective approaches to improving global learning, how governments can develop dynamic and iterative strategies, and the role of private sector partnerships in the successful implementation of EdTech strategies. Keywords: EdTech; education technology; education strategy; best practices for EdTech; EdTech planning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13360175 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1054 ZenodoArchiveConcept: 13360174
Keywords: _r:AddedByMyEducationEvidence

Sandbox Handbook V.2.0 - EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7019219 ZenodoArchiveConcept: 7019218 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7019219 10.53832/edtechhub.0108 2339240:LNQBY8R8 2405685:49ZFP7UN 2405685:MP7LCGPN
Keywords: _r:AddedByZotZen

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen